Advanced systems for improved public healthcare and disease prevention emerging research and opportunities - Edoh, Thierry Oscar, 1968- (Advances in healthcare information systems and administration (AHISA) book series., 2018)
"This book discusses the care delivery issues in global public health care and proposes ICT based solutions for public health care improvement and diseases prevention. It also discusses how to improve the health care by using modern Information and communication technologies, methodologies, frameworks and analyzes the non-technical challenges and make recommendations"--Provided by publisher.